Flexible access to ESA Earth Observation data using JPEG2000 and DRM - Serrão, C.; Carvalho, H.; Dias, J.; Serra, A. (Proceedings of the ESA-EUSC 2006 - Fourth Conference on Image Information Mining for Security and Intelligence, Torrejon air base – Madrid, 2006)
Applications like, change detection, global monitor ing, disaster detection and management have emerging requirements that need the availability of large am ounts of data. This data is currently being capture by a multiplicity of instruments and Earth Observation ( EO) sensors originating large volumes of data that need s to be stored, processed and accessed in order to be us eful. The authors of this paper have been involved on an ESA-sponsored project, called HICOD2000 to study the applicability of the new image encoding standard - JPEG2000 - to EO products. This paper presents and describes the system that was developed for HICOD2000 project, which allows, not only the encoding and decoding of several EO products, but a lso supports some of the security requirements identifi ed previously that allows ESA to define and apply effi cient EO data access security policies and even to exploi t some EO products electronic commerce over the Internet. This system was integrated with the existing ESA Ground Segment systems, specifically the Services Support Environment (SSE).